PENGARUH PENGGUNAAN ALAT PRAKTIKUM UJI ELEKTROLIT TERINTEGRASI MODEL PEMBELAJARAN INKUIRI TERHADAP KETERAMPILAN PROSES SAINS SISWA - Akbar, Jakub Saddam; Mokalu, Yohanes Bery; Rumengan, Stefan Marco; Djakariah, Djakariah; Akbar, Ayu Febrianti; Paat, Meike (LPPM Politeknik Saint Paul Sorong, 2024)
This research examines the effect of electrolyte testing practical equipment integrated with the inquiry learning model on students' science process skills. This research used a pre-experimental design with a one-group pretest-posttest design involving 30 students at MAK Madani Manado. The research results showed a significant increase in students' science process skills, with an average pretest score of 52.48 and posttest of 86.69. This increase reflects the effectiveness of using inquiry-based practical tools in improving skills in observing, classifying, formulating hypotheses, designing experiments, processing data and drawing conclusions. Inquiry learning allows students to participate in the scientific process actively, develop critical thinking skills, and solve problems. These findings positively contribute to creating more innovative and contextual chemistry learning strategies and can be a solution to overcoming limited laboratory facilities in schools